Mathematics education in distance studies - Kasparavičiūtė, Aurelija; Chadyšas, Viktoras (Lietuvos matematikos rinkinys, 2015)
The article elaborated the concept of distance learning and consider distance learning techniques, which are currently used in mathematics education, through distance learning in Vilnius Gediminas Technical University (VGTU).
Keywords: distance learning; mathematics education; moodle system